ANALYSIS OF QUALIFICATIONS AND POSITIONS IN THE POLICE ACADEMY: DOES EDUCATION AFFECT CAREER? - Jarot Muchtar; Muhammad Imam Farid (Pusat Penelitian dan Pengembangan Polri, 2025)
Abstract In law enforcement institutions specially on Police Academy, education and rank are often considered primary factors in determining an individual's career trajectory. However, the extent to which these factors truly influence job placement remains a subject of debate. This study aims to analyze the relationship between educational background and the positions held by Police Academy personnel. The primary motivation of this research is to provide a data-driven approach that can assist in career development planning within the police force. We employ Machine Learning methods, the Random Forest Classifier, to predict job categories based on education and rank. The datasets used in this study includes information on job positions, the most recent police education, the highest general education, rank, and whether the position is structural or functional. The evaluation parameter utilized in this research is the model's accuracy in job classification. The results indicate that education and rank play a significant role in determining a police officer’s career progression. However, the model encounters difficulties in predicting functional job categories, likely due to an imbalanced data distribution.